A Cautious Elite: Toronto's Reluctant Entrance into the Railway Mania of the 1850s - White, William (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
This paper examines the entrepreneurial strategies of Torontonians. It focuses upon public referenda held in 1850 and 1851 to decide whether to invest municipal funds in railways to Lake Huron and Guelph. Historians who have tried to explain why the citizens rejected the investment in the line to Lake Huron and approved the line to Guelph have limited their analyses to the backers of each project. Toronto's merchants opposed the first subscription but approved the second one. The independently wealthy Tories led the promotion in the spring of 1850 but were in the background in the fall of 1851. The meaning seems inescapable: Torontonians responded positively to the appeal of the merchants who appeared to understand, as the Tories did not, the new options open to a community's development which railways created.By concentrating only upon individuals, this analysis ignores the persistence of the developmental attitudes of the 1830s and 1840s. The paper is not concerned with how transportation projects were financed, or the numbers of people, wheat, and hogs which passed over them, but with the style and speculation which attended their discussion. It explains the decisions of 1850-1851 by way of a tradition and briefly examines the responses of Chicagoans to the railway frenzy as a sharpening contrast. Faced with many of the same challenges and possibilities as were the people of Chicago, Torontonians responded with far less confidence and unity. Their own beliefs and values, not those of a Hamilton or a Montreal, were hurdles for the citizens of Toronto. Exuberance over railway schemes only gradually displaced prudent attitudes of the 1830s and 1840s.